(untitled) (Anclajes, 2023)
In 1962, a cultural delegation made up of the painter Servando Cabrera Moreno, the architect Raúl Oliva and the critic and essayist Graziella Pogolotti toured the countries of the Eastern Bloc accompanying an exhibition of contemporary Cuban painting at a critical moment in the Cold War. In the autobiography titled Dinosauria soy: Memorias (2011) and in other shorter writings, Pogolotti gives an account of the ins and outs of this travel in which the artistic proposal of the selected Cuban painters contrasts with the institutional socialist realism of the Soviet sphere. The experience of the Cuban delegation is a practical result of the cultural collaboration agreements and their corresponding annual, biannual or five-year application plans that the Government of Cuba signed with the Eastern Bloc countries starting in 1960, with the aim of establishing and consolidate the bonds of friendship and solidarity of socialism on both sides of the Atlantic.